2015
DOI: 10.14731/kjis.2015.04.13.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Does U.S. Soft Power Have Consequences for U.S. Security? Evidence from Popular Support for Suicide Bombing

Abstract: for comments and suggestions. Mistakes, omissions, and other assorted infelicities are my own responsibility. Data, replication codes and supporting materials are available at http://www.chiozza.or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Results of some studies indicate the possible importance of the combined eff ect (interaction) of two specifi c inequality indicators (e.g. poverty/income and education) (Chiozza 2009;Kavanagh 2011;Saeed and Syed 2018). Other studies suggested the importance of diff erent contextual factors such as level of urbanisation or level of violence (Mousseau 2011;Fair et al 2018).…”
Section: Where When and How Is Inequality Related To Radicalisation?mentioning
confidence: 99%
“…Results of some studies indicate the possible importance of the combined eff ect (interaction) of two specifi c inequality indicators (e.g. poverty/income and education) (Chiozza 2009;Kavanagh 2011;Saeed and Syed 2018). Other studies suggested the importance of diff erent contextual factors such as level of urbanisation or level of violence (Mousseau 2011;Fair et al 2018).…”
Section: Where When and How Is Inequality Related To Radicalisation?mentioning
confidence: 99%
“…It has increased support for US military missions (Goldsmith and Horiuchi, 2012), it has helped to delegitimize terrorist attacks against American citizens (Chiozza, 2015), it has enabled the US to establish military bases in more than 80 countries in all parts of the world (Bitar, 2016), and it has allowed the US to have an outsized influence in the United Nations (Datta, 2009). Support for US leadership has not only been important for the achievement of US foreign policy goals.…”
Section: Introductionmentioning
confidence: 99%